Optimization of High Yield Epoxidation of Malaysian Castor Bean Ricinoleic Acid with Performic Acid - Nadia Salih; Jumat Salimon (Universitas Gadjah Mada, 2022)
Epoxidized castor oil (ECO) has shown high potential for industrial applications as value-added products such as polymer coating, plasticizer, and biolubricant. Epoxidized ricinoleic acid recovered from ECO has potential for industrial usage. In this work, epoxidized ricinoleic acid (ERA) was synthesized through in situ generated performic acid epoxidation of ricinoleic acid (RA). The epoxidation process was optimized by several reaction parameters, such as the molar ratio of formic acid to ethylenic unsaturation, the molar ratio of hydrogen peroxide to ethylenic unsaturation, and reaction temperature. The response reaction parameters of oxirane oxygen content (OOC) and iodine value (IV) were then evaluated. The results showed the optimal condition for the epoxidation of RA was obtained at 50 °C, the molar ratio of formic acid and hydrogen peroxide to ethylenic unsaturation of 1:8:1 for 4 h reaction time. A high yield of ERA of 86% with relative conversion into oxirane of 85.3% was achieved at the optimum condition. The optimum ERA showed a high OOC value of 4.00% and a low IV value of 2.24 mg/g. It is plausible that ERA can be used as an intermediate starting material to prepare value-added products such as biosurfactants, biopolymer additives, or biolubricants.